Combined spatial and dosimetric recurrence pattern analysis in head and neck squamous cell carcinoma following postoperative (chemo)radiotherapy - Schröter, Philipp; Lau, Hoi Hin; Stritzke, Florian; Franke, Henrik; Kozyra, Katharina; Regnery, Sebastian; Bauer, Lukas; Deng, Maximilian; Dvornikovich, Katharina; Hofmann, Anna; Wessels, Lars; Semmelmayer, Karl; et al. (Radiation oncology, 2025)
Advancements in nodal staging for head and neck squamous cell carcinoma (HNSCC) have prompted radiotherapy de-escalation trials to reduce irradiation of electively treated neck regions, with the goal of improving treatment tolerability. While volumetric de-escalation has shown promise in definitive radiotherapy of HNSCC, limited data exist regarding its safety in the postoperative treatment setting. This study aimed to assess dose-level-specific locoregional recurrence patterns following standard postoperative (chemo)radiotherapy in a mixed HNSCC cohort to inform risk-adaptive radiotherapy strategies.
Gesehen am 12.11.2025